A REVIEW: ANTIMICROBIAL AGENTS BASED ON NITROGEN AND SULFUR CONTAINING HETEROCYCLES - Sharma, Praveen Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
At present, heterocyclic compounds and their derived forms have become strong reflection in medicinal research field because of their positive pharmacological and biological properties. Heterocycles are prosperous in nature and have expanded additional importance because their structural subunits are established in many natural products such as antibiotics, vitamins, and hormones. Thiazine moieties present in compounds have multiplicity of medicinal activities such as antihypertensive, antitumor, antimicrobial, antibacterial, anticoagulant, antifungal, anticancer, and antiviral. This review article mainly based on thiazines and their derivatives with potential antimicrobial activities that are at this time in advancement. Keywords: Nitrogen, Sulfur heterocycles (thiazines), Antibacterial, Antifungal, Antimicrobial agents.